PENGARUH STRESS KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA PTPN VII CINTA MANIS - Ninin Non Ayu Salmah (Jurnal Media Wahana Ekonomika, 2015)
The research aim to see the influence of job stress and job satisfaction to the employee performances at PT. Perkebunan Nusantara (PTPN) VII Cinta Manis Ogan Ilir. The employees of PTPN VII Cinta Manis Ogan Ilir is taken as the population. The technique sampling used is simple random sampling. The tools for data analysis are linear regretion, determination coefficient, and hypothesis examination with F-test and t-test. This research results the equation of regression Y=1,984 + 0,235X1 + 0,269X2, The job stress and job satisfaction towards the job performance contributes 34,7%. F-test results in rejection of null  hypothesis and acceptance of alternative hypothesis meaning the job stress and job satisfaction simultaneously influence the job performance significantly. t-test results in rejection of null hypothesis and acceptance of alternative hypothesis meaning the job stress and job satisfaction partially influence towards the job performance of PTPN Cinta Manis Ogan Ilir employees significantly.  Key words: job stress, job satisfaction and employee performance